Multifunctional Modification of SIS Membrane with Chimeric Peptides to Promote Its Antibacterial, Osteogenic, and Healing‐Promoting Abilities for Applying to GBR. (28th May 2021) - Mu, Yuzhu; Ma, Shiqing; Wei, Pengfei; Wang, Yonglan; Jing, Wei; Zhao, Yifan; Zhang, Lei; Wu, Jinzhe; Zhao, Bo; Deng, Jiayin; Liu, Zihao
Abstract: Guided bone regeneration (GBR) technology is the most widely used and stable method for bone defect repair. However, infectious bone defect limits the application of this technique. Herein, a small intestinal submucosa (SIS) membrane modified by chimeric peptides as a new type of GBR membrane is developed for efficacious tissue regeneration. Based on the main components of SIS membrane are I and III collagen, collagen binding peptides TKKTLRT and KELNLVY sequences are used to construct chimeric peptides with healing‐promoting peptide Hst1 or antibacterial osteogenic peptide JH8194, so as to realize the specifically target of SIS. This method achieves the fast and efficient multifunctional modification of SIS membrane. The chimeric peptides modified SIS (pSIS) membrane has satisfactory biocompatibility and a certain degree of antibacterial activity. Moreover, pSIS promotes the osteogenic related factors expression of rat bone mesenchymal stem cells and demonstrates great bone regeneration in rat skull defect model. Furthermore, pSIS accelerates the migration of oral epithelial cells in vitro and activate integrin α3β1 signal pathway contribute to wound healing. This study presents a novel biomaterial design of GBR membrane, specifically for the treatment of infectious bone defects. Abstract : Collagen binding peptides TKKTLRT and KELNLVY are connected with JH8194 or Hst1 to construct chimeric peptides, which can specifically bind to the surface of the small intestinal submucosa (SIS) membrane quickly and effectively to realize modification. The chimeric peptides modified SIS membrane has osteogenic, healing‐promoting, and antibacterial biofunctions which can be used as a novel guided bone regeneration membrane.